2012
DOI: 10.1016/j.tetlet.2012.05.154
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent iodine(V) mediated mild and convenient synthesis of substituted 2-amino-1,3,4-oxadiazoles

Abstract: a b s t r a c tA simple protocol for the synthesis of 2-amino-1,3,4-oxadiazoles starting from the corresponding acylhydrazides by cyclodesulfurization of intermediate acylthiosemicarbazides mediated by o-iodoxybenzoic acid in good yields has been described. The protocol is mild with wide substrate scope, and thus a range of 2-amino-1,3,4-oxadiazoles have been prepared.Ó 2012 Elsevier Ltd. All rights reserved.1,3,4-Oxadiazoles have found extensive use as pharmacophores due to their metabolic profile and ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…It was observed that the higher temperature and presence of aromatic or electron withdrawing groups were necessary for effective deselenizaton/cyclization and longer reaction time up to 24 h was required for the cyclization at lower temperatures. In continuation of our studies on desulfurization/ deselenization using iodine reagents for the synthesis of 2‐amino‐1,3,4‐oxadiazoles,, we describe a novel I 2 mediated synthesis of 2‐iminohydantoins and 2‐amino‐1H‐imidazol‐4(5H)‐ones from selenourea tethered amides/peptides.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the higher temperature and presence of aromatic or electron withdrawing groups were necessary for effective deselenizaton/cyclization and longer reaction time up to 24 h was required for the cyclization at lower temperatures. In continuation of our studies on desulfurization/ deselenization using iodine reagents for the synthesis of 2‐amino‐1,3,4‐oxadiazoles,, we describe a novel I 2 mediated synthesis of 2‐iminohydantoins and 2‐amino‐1H‐imidazol‐4(5H)‐ones from selenourea tethered amides/peptides.…”
Section: Introductionmentioning
confidence: 99%
“…2‐Amino‐5‐substituted‐1,3,4‐oxadiazoles can be synthesized by the cyclization of corresponding diacylhydrazines or thiosemicarbazide (Fig. D) . Few amino‐acid‐derived 2‐amino‐1,3,4‐oxadiazoles are reported in the literature by the treatment of CNBr with hydrazide .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, cyclodehydration of N , N ′-diacylhydrazines is carried out using reagents such as PPA [ 18 ], H 2 SO 4 [ 19 ], SOCl 2 [ 20 , 21 ], POCl 3 [ 22 , 23 ], P 2 O 5 [ 24 ] (CF 3 SO 2 ) 2 O [ 25 ], BF 3 ·OEt 2 [ 26 ] or the Burgess reagent [ 27 ]. 1,3,4-Oxadiazole derivatives may also be prepared by oxidative cyclization of N -acylhydrazones with oxidizing agents such as CAN [ 28 ], KMnO 4 [ 29 ], FeCl 3 [ 30 ], Br 2 [ 31 ], PbO 2 [ 32 ], chloramine T [ 33 ], HgO/I 2 [ 34 ], hypervalent iodine reagents [ 35 41 ]. One-pot syntheses of these compounds from acid hydrazides with carboxylic acids [ 42 ] or orthoesters [ 43 45 ] in the presence of an acidic catalyst have also been reported.…”
Section: Introductionmentioning
confidence: 99%